Untranslatability Within and Beyond Lexical Level in Arabic-English Translation - Alajmi, Fhaid Saad (Journal of Posthumanism, 2025)
This paper primarily explores the concept of Untranslatability and how Translation Studies’ definition impacts its meaning and made it a nemesis of religious and poetic texts. The key significance of this study is how untranslatability occurs at and beyond lexical levels. At lexical level, is discusses how the Quranic masculine singular pronoun “هو” in reference to the Islamic God is untranslatable due to the distinction both Arabic and English have. Whereas poetry is discussed beyond the lexical level to showcase the impossibility of rendering both sense and style from Arabic into English. The study discussion revealed that sacred scripters should never be translated but rather explained and that poetry is impossible to translate if the purpose is to maintain both style and meaning.